Determinants of corruption in developing countries - Mumtaz Anwar Chaudhry; Ghulam Shabbir (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
Corruption is not a new phenomenon; we are living with it since the birth of government's institutions. Corruption has two dimensions; public sector corruption and private sector corruption. The public sector corruption means, misuse of public office for private benefits. For cross country analysis, public sector corruption is mainly focused. In this study, we have analyzed the 41 developing countries to investigate the determinants of corruption. Corruption determinants are sub-divided into economic determinants and non-economic determinants. The economic determinants include economic freedom, globalization, level of education, distribution of income and average level of income. The non-economic determinants list consists on press freedom, democracy and share of population affiliated with particular religion. The empirical findings of the study indicates that; all economic determinants are negatively related to the perceived level of corruption except distribution of income and non-economic determinants are not significantly explaining the variations in the level of corruption. This shows that the socio-political and religious norms are so weak that they can not affect the corruption level in these countries. The contribution of religion in people's practical life is very little, so the cultural values of developing countries are not religion based. Therefore, perceived level of corruption is not affected by the religion. This study concluded that government should focus the economic factors to curb the level of corruption.
Keywords: 330